2013
DOI: 10.1158/0008-5472.can-13-0382-t
|View full text |Cite
|
Sign up to set email alerts
|

An Essential Requirement for the SCAP/SREBP Signaling Axis to Protect Cancer Cells from Lipotoxicity

Abstract: SREBPs are key transcriptional regulators of lipid metabolism and cellular growth. It has been proposed that SREBP signaling regulates cellular growth through its ability to drive lipid biosynthesis. Unexpectedly, we find that loss of SREBP activity inhibits cancer cell growth and viability by uncoupling fatty acid synthesis from desaturation. Integrated lipid profiling and metabolic flux analysis revealed that cancer cells with attenuated SREBP activity maintain long-chain saturated fatty acid synthesis, whil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
139
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(146 citation statements)
references
References 36 publications
2
139
0
Order By: Relevance
“…SCD1 is suggested be a major driver of fatty acid synthesis from glucose (46) and has also been shown to help negotiate cellular stress, with SCD1 inhibition leading to saturated fatty acid accumulation, toxicity, and endoplasmic reticulum stress (40,47,48). This is likely to be of particular importance in the cancer phenotype where levels of saturated fatty acid synthesis are often high (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…SCD1 is suggested be a major driver of fatty acid synthesis from glucose (46) and has also been shown to help negotiate cellular stress, with SCD1 inhibition leading to saturated fatty acid accumulation, toxicity, and endoplasmic reticulum stress (40,47,48). This is likely to be of particular importance in the cancer phenotype where levels of saturated fatty acid synthesis are often high (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…SCAP is a regulatory element binding protein (SREBP) cleavage-activating protein (SCAP). SCAP gene plays important role as a sterol sensor (Espenshade, 2006) as well as a transcriptional regulator of lipid metabolism and cellular growth (Williams et al, 2013). Previous research has shown that androgen (therapeutics agent used for advanced prostate cancer) has increased the expression of SCAP suggesting lipogenic effect of this agent in prostate cancer cells (Heemers et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…One microliter of sample was injected in split mode. Full oven program and MS settings are available upon request (55). MS detector was run in SIM mode.…”
Section: Gc/ms Analysismentioning
confidence: 99%